هنري كيسنجر والصراع العربي الإسرائيلي (1970-1982) - بوختالة سميرة (جامعة محمد بوضياف بالمسيلة, 2025)
تتناول هذه المذكرة دور هنري كيسنجر في الصراع العربي الإسرائيلي خلال السبعينات والثمانينات. يحلل البحث تطور الصراع منذ 1948 حتى 1970، ثم يركز على دور كيسنجر كوزير خارجية أمريكي في حرب أكتوبر 1973 ودبلوماسيته المكوكية. تُظهر الدراسة كيف نجح كيسنجر في التوصل لاتفاقيات فض الاشتباك بين مصر وإسرائيل (1974-1975) وسوريا وإسرائيل (1974)، وكيف مهدت جهوده لمعاهدة كامب ديفيد 1978. يخلص البحث إلى أن كيسنجر نجح في تفكيك الوحدة العربية وإخراج مصر من الصراع، مما أضعف القضية الفلسطينية. This thesis examines Henry Kissinger's role in the Arab-Israeli conflict during the 1970s and 1980s. The research analyzes the evolution of the conflict from 1948 to 1970, then focuses on Kissinger's role as U.S. Secretary of State during the October War of 1973 and his shuttle diplomacy. The study demonstrates how Kissinger successfully negotiated disengagement agreements between Egypt and Israel (1974-1975) and Syria and Israel (1974), and how his efforts paved the way for the Camp David Accords of 1978. The research concludes that Kissinger succeeded in fragmenting Arab unity and removing Egypt from the conflict, thereby weakening the Palestinian cause. Keywords: Henry Kissinger - Arab-Israeli Conflict - October War 1973 - Shuttle Diplomacy - Disengagement Agreements - Camp David - American